Analysis of the Effect of Tax Revenue and Government Expenditure on the Education Sector on the Human Development Index in ASEAN-6 Countries - Nova Fatimah; Anna Yulianita; Siti Rohima; Imam Asngari; Abdul Bashir (JURNAL ECONOMINA, 2026)
This study aims to examine the effect of government expenditure on the health and education sectors on the Human Development Index (HDI) in six major ASEAN countries (Indonesia, Malaysia, Thailand, the Philippines, Singapore, and Vietnam) during the 2012–2021 period. The data were obtained from three primary sources: the Organisation for Economic Co-operation and Development (OECD), the United Nations Development Programme (UNDP), and the World Bank. The study employs multiple linear regression with a panel data approach. Prior to the estimation, a series of classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests were conducted to ensure the validity and reliability of the regression model. The results indicate that government expenditure on the health and education sectors has a positive and statistically significant effect on the HDI of ASEAN-6 countries. These findings underscore the importance of effective budget allocation in the social sector to promote sustainable human development across the ASEAN region and provide strategic policy implications for governments in designing budget allocation policies that prioritize the education sector to improve people's quality of life.